2010
DOI: 10.1186/1471-2180-10-291
|View full text |Cite
|
Sign up to set email alerts
|

Pellicle formation in Shewanella oneidensis

Abstract: BackgroundAlthough solid surface-associated biofilm development of S. oneidensis has been extensively studied in recent years, pellicles formed at the air-liquid interface are largely overlooked. The goal of this work was to understand basic requirements and mechanism of pellicle formation in S. oneidensis.ResultsWe demonstrated that pellicle formation can be completed when oxygen and certain cations were present. Ca(II), Mn(II), Cu(II), and Zn(II) were essential for the process evidenced by fully rescuing pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 59 publications
3
72
0
Order By: Relevance
“…Results showed that the EPS profiles of these two strains were virtually identical, eliminating the possibility. Notably, in agreement with the previous finding by Liang et al (44), D-glucose and D-mannose were the major monosaccharide units of EPS in S. oneidensis. These data collectively suggest that the rugose morphotype of fliF1 is due to a mechanism other than increased production of EPS.…”
Section: Resultssupporting
confidence: 82%
“…Results showed that the EPS profiles of these two strains were virtually identical, eliminating the possibility. Notably, in agreement with the previous finding by Liang et al (44), D-glucose and D-mannose were the major monosaccharide units of EPS in S. oneidensis. These data collectively suggest that the rugose morphotype of fliF1 is due to a mechanism other than increased production of EPS.…”
Section: Resultssupporting
confidence: 82%
“…The bpfA operon in Shewanella species such as S. oneidensis MR-1 and S. putrefaciens CN32 commonly contains seven genes, including a TISS for BpfA translocation. Disruption of the TISS blocks formation of pellicle, a type of biofilm formed at the air-liquid interface which is probably caused by interruption of BpfA translocation (21). A hyper-aggregating mutant of S. oneidensis MR-1 with enhanced biofilm formation exhibits increased transcription of a TISS component up to about 5-fold, and inactivation of the TISS results in the loss of the hyper-aggregation phenotype (22).…”
mentioning
confidence: 99%
“…The beakers were kept still for pellicle formation at the room temperature. Cells in pellicle and underneath were separated based on published paper (Liang et al 2010). To quantify the pellicles formed by the S. oneidensis wild-type and mutant strains, cells from pellicles were collected, suspended in 30 ml fresh LB, violently vortexed, and applied to the spectrometer at 600 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Three genes encoding TISS proteins were consistently up-regulated in pellicle cells. Our previous data showed that the pellicle was severely deWcient in the in-frame deletion mutant of aggA which blocked secretion via TISS (Liang et al 2010). Mutants carrying in-frame deletion in one of targeted genes were constructed.…”
Section: Mutational Analysis Of Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation